ANALISIS PENDAPATAN USAHATANI PADI SAWAH DI DESA BERABAN KECAMATAN BALINGGI KABUPATEN PARIGI MOUTONG - Moh Resky Nugraha; Dance Dance; Made Krisna Laksmayani (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
This study aims to determine the income of lowland rice farming in Beraban Village, Balinggi District, Parigi Moutong Regency. This research was conducted in Beraban Village, Balingi District, Parigi Moutong Regency from September to December 2019. There were 30 respondents with a population of 125 rice farmers. The analytical method used is income analysis. The results of the analysis show that the average income of lowland rice farming is Rp. 43,934,598.10/2.40ha or Rp. 18,306,082.54/ha, the average income from lowland rice farming is Rp. 64,919,032.26/2.40ha or Rp. 27,049,596.77/ha, and the average total cost is Rp. 20,984,434.00/2.40 ha or Rp. 8,752,926/ha. This value shows that the total revenue is greater than the costs incurred by clove farmers in Beraban Village